MXene-Based Photothermal Fabrics Via Dip-Coating for Solar-Driven Evaporation Of Seawater - Mohd Haiqal Abd Aziz; Nik Alwi, Nik Ashraf Daniel; Abdul Khalil, Ahmad Faez; Alias, Nur Hashimah (Journal of Advanced Industrial Technology and Application, 2024)
Solar-driven interface evaporation (SDIE) is a promising and sustainable seawater desalination approach that can perform long-term application. Unlike conventional desalination method, which does not support in off grid area, SDIE offers a viable solution because of its reliance on solar energy and its simple setup. In this work, a MXene/Polypyrrole (PPy) cotton-based fabric was prepared via a dip-coating method to serve as the SDIE system's solar absorber. The MXene and PPy modification endows the fabric with excellent photothermal ability. The optimal MXene/PPy fabric was determined based on two factors (volume of MXene and PPy) and two responses  (surface temperature and coating stability). The optimized MXene/PPY fabric, containing 3 ml of MXene and 100 µl of pyrrole, demonstrated minimal coating leaching of 0.026 grams with the ability to provide surface temperature of 64°C. Outdoor performance testing under sunny day showed an average evaporation rate of 0.041 L/m²·h with low conductivity of 0.347 µS/cm, indicating its effectiveness in desalination applications